Effects of high mobility group protein box 1 and toll like receptor 4 pathway on warts caused by human papillomavirus - WENG, HUI (D.A. Spandidos, 2014)
Accumulative evidence has demonstrated that inflammation has an important role in human papillomavirus (HPV) oncogenicity. However, the effects of high mobility group protein box 1 (HMGB1)-toll like receptor 4 (TLR4) signaling pathway associated inflammation on epidermal warts caused by HPV remain unclear. The present study investigated the HMGB1, TLR4 and nuclear factor-κB p65 expression in condyloma acuminatum (CA) and verruca vulgaris (VV). Immunohistochemistry and western blot analysis revealed that p65 expression in epithelial nuclei in VV and CA was significantly higher than in normal skin (NS) (P<0.01), and p65 in CA was higher than in VV but this difference was not significant. The level of extracellular HMGB1 increased significantly and progressively from NS to VV to CA (P<0.05). The level of TLR4 on the surface of epithelial membranes in the CA samples was significantly higher than in NS (P<0.01), and TLR4 in VV samples was significantly lower than in NS (P<0.01). There was a positive correlation between p65 expression in the epithelial nuclei and HMGB1 in the epithelial intercellular spaces (r=0.5199, P<0.01). These findings indicate that inflammation is intensified in warts caused by HPV. HMGB1-TLR4 pathway-associated inflammation may therefore have a pivotal role in CA. HMGB1, rather than TLR4, may be a vital mediator of inflammation in VV. Therapies targeting HMGB1 may be a potential strategy for the treatment of HPV-associated warts.